2022
DOI: 10.1002/trc2.12357
|View full text |Cite
|
Sign up to set email alerts
|

The role of dyadic cognitive report and subjective cognitive decline in early ADRD clinical research and trials: Current knowledge, gaps, and recommendations

Abstract: Efficient identification of cognitive decline and Alzheimer's disease (AD) risk in early stages of the AD disease continuum is a critical unmet need. Subjective cognitive decline is increasingly recognized as an early symptomatic stage of AD. Dyadic cognitive report, including subjective cognitive complaints (SCC) from a participant and an informant/study partner who knows the participant well, represents an accurate, reliable, and efficient source of data for assessing risk. However, the separate and combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 129 publications
(359 reference statements)
2
12
0
Order By: Relevance
“…Previous studies typically have been conducted at single research centers, have had a relatively small sample size, and have specifically asked participants about their cognition, which precludes unprompted reporting and may affect the results (eg, overreporting of cognitive complaints). PD‐PROP is accessible to PD patients broadly, has a very large sample size, and asks PwP to generate their own list of problems without the imposing interaction of a clinician interview, although it is possible that obtaining input from both a patient and an informant 29,30 or objective testing of cognitive functional abilities 31 may be more accurate than only patient self‐report, given reported deficits in self‐awareness of cognitive functional abilities in PD, particularly as cognition declines 32 . Our cohort included a wide range of participants in terms of sex, age, and disease duration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies typically have been conducted at single research centers, have had a relatively small sample size, and have specifically asked participants about their cognition, which precludes unprompted reporting and may affect the results (eg, overreporting of cognitive complaints). PD‐PROP is accessible to PD patients broadly, has a very large sample size, and asks PwP to generate their own list of problems without the imposing interaction of a clinician interview, although it is possible that obtaining input from both a patient and an informant 29,30 or objective testing of cognitive functional abilities 31 may be more accurate than only patient self‐report, given reported deficits in self‐awareness of cognitive functional abilities in PD, particularly as cognition declines 32 . Our cohort included a wide range of participants in terms of sex, age, and disease duration.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, a more nuanced understanding of how demographic and modifiable factors contribute to participant‐ and SP‐reported SCD also has the potential to inform research recruitment/design 41 and interventions. Recent studies have identified aspects of SCD (e.g., onset of cognitive decline in the past 5 years, worry about decline, and SP concern of decline) that best predict AD pathology, referred to as SCD‐plus 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Ideally the study partner knows the participant well enough to be able to provide insight into the current status of, and recent changes in, the participant's cognitive and functional abilities. 1,2 Advantages of involving dyads in research include (1) efficient, accurate, and reliable data for assessing ADRD risk 3,4 ;…”
Section: Introductionmentioning
confidence: 99%